Modelling marketing resources, procurement process coordination and firm performance in the building construction industry: the integration of resource based view and coordination theories / Akmal Aini Othman - Othman, Akmal Aini (2011)
The construction industry is a complex and the most people-intensive sector in the national economy. While it forms a major pillar to a nation’s socio-economic development, past studies have found that this industry, with particular reference to the building materials resources, were not sufficiently managed, leading to a waste of bad material management with time and cost overrun. Problems in the inaccuracy of data, unplanned deliveries, wrong and defective deliveries for instance, require the supply chain members to be coordinated. In view of this, there is a need to investigate the procurement process coordination (PPC) between the contractor and his building materials suppliers, focusing on the opportunities of the improvement in operational and customer performance. Thus, the present study looked into the coordination between the construction firm and its main building materials suppliers to allow for greater understanding in the field of supply chain management (SCM). Drawing upon two theories namely Resource Based View (RBV) and Coordination Theory (CT), it also analysed the relationship of the three critical constructs; marketing resources, PPC and firm performance. This study intended to shed light into the potential implication of the link in a more coherent and integrated approach particularly from the lens of construction supply chain. With this backdrop, the objective of the study was formulated to establish a link between these constructs (marketing resources, PPC and firm performance) and their dimensions as well as to examine the mediating role of PPC on this link. This study contributes to the new knowledge by detailing the activities involved in PPC instead of testing it in a general setting. Data for this study was gathered through a survey questionnaire. The analysis was conducted using Structural Equation Modelling (SEM) technique by examining two competing models that represent full and partial mediation. The findings revealed that marketing resources have positive and significant effects on PPC dimensions. It was also found that PPC fully mediates the relationship between marketing resources and firm performance. Result from the Sobel test provides evidence that joint operational planning and supplier relationship development appeared to confirm their role as mediating factor in the relationship between marketing resources and firm performance. In other words these two dimensions of PPC facilitate the conversion of marketing resources into firm performance. This finding was consistent with the movement of the industry players towards ‘best practices’ which emphasised on SCM, client orientation and innovativeness. Following these findings, a number of implications are offered for the construction industry. First, construction industry players should adopt and emphasis on such orientations in order to enhance their performance particularly with the operational and customer performance. Second, PPC, in particular join decision planning and supplier relationship development provided greater room for understanding on the impact of marketing resources on the effectiveness and efficiency of the construction supply chain. Finally, the industry players must act upon the importance of marketing resources in order to optimise their supply chain coordination capability.